Optimizing first-line TKI treatment efficacy in PD-L1-positive EGFR-mutated NSCLC: the impact of antiangiogenic agents - Xuanhong Jin; Yang Pan; Cheng Cheng; Hangchen Shen; Chongya Zhai; Kailai Yin; Xinyu Zhu; Hongming Pan; Liangkun You (Frontiers Media S.A., 2024)
BackgroundIn individuals receiving treatment with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), those exhibiting positive PD-L1 expression might experience reduced progression-free survival (PFS). However, the effects on overall survival (OS) and the determination of efficacious treatment approaches are still not well-defined.MethodsIn our retrospective study, we examined data from 193 NSCLC patients with advanced EGFR mutations who received first-line TKI treatments, treated at two centers of Shaw Hospital in Zhejiang, China. This analysis covered a period from 1 January 2016 to 30 April 2023.ResultsPatients with PD-L1 positivity exhibited a markedly shorter average PFS (9.5 months versus 17.8 months, P < 0.001) and OS (44.4 months versus 65.7 months, P = 0.016) relative to those without PD-L1 expression. This difference in both PFS and OS remained statistically significant even after adjusting for multiple factors (P < 0.001 for PFS and P = 0.028 for OS). In the PD-L1-positive cohort, introducing combination antiangiogenic significantly extended both PFS (from 9.1 to 25.7 months, P = 0.026) and OS (from 42 to 53.5 months, P = 0.03). Post-first-line TKI therapy, 39.3% of PD-L1-positive patients and 54.5% of PD-L1-negative patients developed the T790M mutation (P = 0.212), with no notable difference in PFS from second-line TKI treatments between the groups. Additionally, subsequent combination therapy with immunotherapy markedly prolonged OS in the PD-L1-positive group. However, for PD-L1-negative patients, neither combination antiangiogenic therapy nor later-line immunotherapy demonstrated significant benefits in PFS or OS.ConclusionFor PD-L1-positive patients, combined antiangiogenic treatments and immunotherapy can significantly improve survival outcomes. In contrast, PD-L1-negative patients show less benefit from these therapies, highlighting the greater efficacy of these treatments in PD-L1-positive individuals.